Chemogenetic modulation of the rat locus coeruleus alters hippocampal noradrenaline release and modulates perforant path-evoked responses - Caestecker, Sielke; Lescrauwaet, Emma; Vonck, Kristl; Sprengers, Mathieu; Carrette, Evelien; Boon, Paul; Larsen, Lars Emil; Raedt, Robrecht (Frontiers in Neuroscience, 2025)
IntroductionThe locus coeruleus (LC)—noradrenaline (NA) system plays a crucial role in modulating neuronal excitability and plasticity. In epilepsy, the LC-NA system plays an important role in regulating seizure thresholds and severity, with elevated NA release mediating the seizure-suppressing effects of vagus nerve stimulation (VNS). We investigated whether chemogenetic LC activation is able to increase hippocampal NA release and affect hippocampal electrophysiology in anesthetized rats.Methods22 male Sprague—Dawley rats were injected with the viral vector AAV9-hSyn-NE2m in the hippocampus to induce expression of the GRABNE2m biosensor to locally measure changes in extracellular NA. 15/22 rats were injected with the CAV2-PRSx8-hM3Dq hSyn-mCherry viral vector in the LC to express the excitatory DREADD hM3Dq, allowing LC activation with deschloroclozapine (DCZ), and 7/22 with CAV2-PRSx8-GtACR2 as a control. A perforant path stimulation electrode and a dentate gyrus (DG) recording electrode were implanted for local field potential (LFP) and evoked potential (EP) recording as well as a DG optical fiber for GRABNE2m fluorescence measurement.ResultsIn a significant number of rats (7/15) we found an increase in hippocampal NA release, field excitatory post synaptic potential (fEPSP) slope and population spike (PS) amplitude, indicating an increase in excitatory neurotransmission and neuronal output. 4/15 rats showed a decrease in NA release without changes in fEPSP slope or PS amplitude, and 4/15 showed no change in NA release.DiscussionThese findings indicate that chemogenetic activation of the LC-NA system can modulate hippocampal evoked responses, supporting further exploration of its role in health and disease, such as in epilepsy.